The Price Effect of Initial Public Offerings on The Warsaw Stock Exchange - Jarosław KUBIAK; Mateusz SKWAREK (Communications of International Proceedings, 2021)
The Warsaw Stock Exchange (WSE) is the largest stock exchange in Central and Eastern Europe, and one of the fastest growing. Improvements in the capital market infrastructure have led to its recent reclassification to Develped Market status. This makes the Polish stock exchange an interesting and important research area. The paper has two main objectives. Firstly, we update the previous findings on the phenomena of short-run underpricing and long-run overpricing of IPO on the Polish capital market. Secondly, the research aims to check whether short-term and longterm price behavior is related to changes in stock market cycles. The occurrence of short-term underpricing and the effects of long-term underperformance on financial markets are of major importance for both companies raising capital and investors. We investigate short- and long-term IPO reactions to initial public offerings in Poland on the WSE with a more up-to-date sample than in previous studies. The price performance of IPO firms was observed using an event analysis study. The research allows the conclusion that IPO underpricing in the short term exists on the Polish stock market, similar to most worldwide markets. The obtained results confirmed that IPO first-day returns on the WSE decreased as time passed. This may suggest an improvement in the efficacy of the Polish stock market over time. For a short term, during the upward trend on the WSE, the returns were only positive. It may be noted that this tendency in the short run can be linked with herding behavior and investors' perceptions.
Keywords: IPO; underpricing; overpricing; event studies; Warsaw Stock Exchange